Neuroleptic malignant syndrome induced by concomitant use of risperidone and quetiapine - Mustafa Volkan Demir; Tuba Ozturk Demir; Selcuk Yaylaci; Huseyin Yildiz; Ibrahim Tayci; Mustafa Baydar (Wolters Kluwer Medknow Publications, 2016)
Neuroleptic malignant syndrome (NMS) is a rare but life-threatening condition induced by neuroleptic medications. In severe cases, NMS can rapidly lead to death. NMS is reported less frequently now-a-days with the advent of new antipsychotic drugs. We discuss 20-year-old male patient with NMS induced by risperidone and quetiapin.